\(x2 - 5x -2√3x + 12 = 0\)

\(√\)(

K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

25 tháng 6 2018

a) \(2\sqrt{2x}-5\sqrt{8x}+7\sqrt{18x}=28\) (*)

đk: x >/ 0

(*) \(\Leftrightarrow2\sqrt{2x}-10\sqrt{2x}+21\sqrt{2x}=28\)

\(\Leftrightarrow13\sqrt{2x}=28\) \(\Leftrightarrow\sqrt{2x}=\dfrac{28}{13}\Leftrightarrow2x=\left(\dfrac{28}{13}\right)^2\Leftrightarrow x=\dfrac{392}{169}\left(N\right)\)

Kl: \(x=\dfrac{392}{169}\)

b) \(\sqrt{4x-20}+\sqrt{x-5}-\dfrac{1}{3}\sqrt{9x-45}=4\) (*)

đk: x >/ 5

(*) \(\Leftrightarrow2\sqrt{x-5}+\sqrt{x-5}-\sqrt{x-5}=4\)

\(\Leftrightarrow2\sqrt{x-5}=4\Leftrightarrow\sqrt{x-5}=2\Leftrightarrow x-5=4\Leftrightarrow x=9\left(N\right)\)

Kl: x=9

c) \(\sqrt{\dfrac{3x-2}{x+1}}=2\) (*)

Đk: \(\left[{}\begin{matrix}x< -1\\x\ge\dfrac{2}{3}\end{matrix}\right.\)

(*) \(\Leftrightarrow\dfrac{3x-2}{x+1}=4\Leftrightarrow3x-2=4x+4\Leftrightarrow x=-6\left(N\right)\)

Kl: x=-6

d) \(\dfrac{\sqrt{5x-4}}{\sqrt{x+2}}=2\) (*)

Đk: \(x\ge\dfrac{4}{5}\)

(*) \(\Leftrightarrow\sqrt{5x-4}=2\sqrt{x+2}\Leftrightarrow5x-4=4x+8\Leftrightarrow x=12\left(N\right)\)

Kl: x=12

10 tháng 10 2019

a, Điều kiện x ∉ {\(\frac{5}{3};\frac{1}{7}\)}

\(\sqrt{3x-5}=\sqrt{7x-1}\)

\(\left(\sqrt{3x-5}\right)^2=\left(\sqrt{7x-1}\right)^2\)

\(\left|3x-5\right|=\left|7x-1\right|\)

\(3x-5=7x-1\)

\(-4x=4\) => x = -1

AH
Akai Haruma
Giáo viên
4 tháng 7 2019

Lời giải:

a) Theo định lý Vi-et:

\(\left\{\begin{matrix} x_1+x_2=\frac{-3}{4}\\ x_1x_2=\frac{-m^2+3m}{4}\end{matrix}\right.\Leftrightarrow \left\{\begin{matrix} -2+x_2=\frac{-3}{4}\\ (-2)x_2=\frac{-m^2+3m}{4}\end{matrix}\right.\)

\(\Leftrightarrow \left\{\begin{matrix} x_2=\frac{5}{4}\\ (-2)x_2=\frac{-m^2+3m}{4}\end{matrix}\right.\)

\(\Rightarrow \frac{-m^2+3m}{4}=(-2).\frac{5}{4}=\frac{-10}{4}\)

\(\Rightarrow -m^2+3m=-10\)

\(\Leftrightarrow m^2-3m-10=0\Leftrightarrow (m-5)(m+2)=0\Rightarrow \left[\begin{matrix} m =5\\ m=-2\end{matrix}\right.\)

b)

Theo định lý Vi-et \(\left\{\begin{matrix} x_1+x_2=\frac{2(m-3)}{3}\\ x_1x_2=\frac{5}{3}\end{matrix}\right.\Leftrightarrow \left\{\begin{matrix} \frac{1}{3}+x_2=\frac{2(m-3)}{3}\\ \frac{1}{3}x_2=\frac{5}{3}\end{matrix}\right.\)

\(\Leftrightarrow \left\{\begin{matrix} \frac{1}{3}+x_2=\frac{2(m-3)}{3}\\ x_2=5\end{matrix}\right.\)

\(\Rightarrow \frac{2(m-3)}{3}=\frac{1}{3}+5=\frac{16}{3}\)

\(\Rightarrow 2(m-3)=16\Rightarrow m=11\)

AH
Akai Haruma
Giáo viên
18 tháng 6 2019

Lời giải:

a) Theo định lý Vi-et:

\(\left\{\begin{matrix} x_1+x_2=\frac{-3}{4}\\ x_1x_2=\frac{-m^2+3m}{4}\end{matrix}\right.\Leftrightarrow \left\{\begin{matrix} -2+x_2=\frac{-3}{4}\\ (-2)x_2=\frac{-m^2+3m}{4}\end{matrix}\right.\)

\(\Leftrightarrow \left\{\begin{matrix} x_2=\frac{5}{4}\\ (-2)x_2=\frac{-m^2+3m}{4}\end{matrix}\right.\)

\(\Rightarrow \frac{-m^2+3m}{4}=(-2).\frac{5}{4}=\frac{-10}{4}\)

\(\Rightarrow -m^2+3m=-10\)

\(\Leftrightarrow m^2-3m-10=0\Leftrightarrow (m-5)(m+2)=0\Rightarrow \left[\begin{matrix} m =5\\ m=-2\end{matrix}\right.\)

b)

Theo định lý Vi-et \(\left\{\begin{matrix} x_1+x_2=\frac{2(m-3)}{3}\\ x_1x_2=\frac{5}{3}\end{matrix}\right.\Leftrightarrow \left\{\begin{matrix} \frac{1}{3}+x_2=\frac{2(m-3)}{3}\\ \frac{1}{3}x_2=\frac{5}{3}\end{matrix}\right.\)

\(\Leftrightarrow \left\{\begin{matrix} \frac{1}{3}+x_2=\frac{2(m-3)}{3}\\ x_2=5\end{matrix}\right.\)

\(\Rightarrow \frac{2(m-3)}{3}=\frac{1}{3}+5=\frac{16}{3}\)

\(\Rightarrow 2(m-3)=16\Rightarrow m=11\)

14 tháng 8 2019

\(a,x-3\sqrt{x}+2\)

\(=x-3\sqrt{x}+\frac{9}{4}-\frac{1}{4}\)

\(=\left(x-\frac{3}{2}\right)^2-\left(\frac{1}{2}\right)^2=\left(x+2\right)\left(x-2\right)\)

14 tháng 8 2019

câu a mình nhìn nhầm :

\(=\left(x-1\right)\left(x+2\right)\)

11 tháng 6 2018

@Hắc Hường

25 tháng 6 2019

\(=\frac{\sqrt{2}}{2}-\frac{3}{2}.\frac{3\sqrt{2}}{2}+\frac{2}{5}.5\sqrt{2}=\frac{\sqrt{2}}{2}-\frac{9}{2\sqrt{2}}+2\sqrt{2}\)

\(=\frac{2-9+8}{2\sqrt{2}}=\frac{1}{2\sqrt{2}}=\frac{\sqrt{2}}{4}\)